PENGELOLAAN PEMBIAYAAN KEUANGAN DAN PEMBERIAN KREDIT DALAM PERKEMBANGAN USAHA MIKRO KECIL DAN MENENGAH DI INDONESIA - Ratiyah Ratiyah (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2016)
UKM currently a priority in the planning stages of development under the supervision of the Ministry of Industry and Trade, and the Ministry of Cooperatives and UKM considering most people more perperan in UKM compared to large businesses. Status of UKM is currently well placed to lift the economy of the people, especially in the era of the MEA, the independence of UKM expected to be achieved in the future so that the development of the people's economy is expected to increase people's income, employment opportunities, and prosperity of the society as a whole. Development of Micro, Small and Medium Enterprises (UMKM) are usually accompanied with capital requirements. In these conditions usually UKM can’t develop its business further, due to lack of funds. Hence the importance of capital lending institutions to play a role, as well as put through mentoring. Facilitate access to capital sources will solve the problem of the company's capital needs. The data used are secondary data from Bank Indonesia, BPS and the Ministry of Cooperatives and UKM in the form of monthly data for 2 years ie 2011 and 2012 (time series). Once the data is collected, the data were analyzed using multiple regression method with SPSS version 18.00. Simultaneously we can conclude cost factors such as inflation and interest rates negatively affect asset growth of UKM, while crediting positive effect of increasing the assets of UKM. While in general, these studies have significant influence 0:01, because Fsig value is 0.000, less than the real level. Keywords: Financing Finance, Credit, and Micro Small And Medium Enterprises